PERSPEKTIF AL-QUR’AN TENTANG TOLERANSI BERAGAMA - Budi Suhartawan; Haris Renaldi (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
The Al-Quran's perspective on religious tolerance is part of the attitude of bringing peace, ease, openness of heart, respecting differences without insulting each other and carried out consistently and sustainably. Both in essence and natural teachings, ingrained and rooted. The application of all of this is being able to build unity and oneness between the nation's children in building national and state harmony and obeying the religion they adhere to. The type of research used is library research, using reference sources in the form of books, tafsir books, journals, documents and so on. The Al-Qur'an perspective on religious tolerance is reflected in four categories; First, be smart in increasing religious understanding, second, do not risk your beliefs in the name of religious tolerance. Third, do not spread hate speech by insulting, making fun of, criticizing, or calling someone who is of a different religion, ethnicity or race with bad titles; and fourth, do not force other people to embrace the teachings of the religion they adhere to.